2017
DOI: 10.1038/s41598-017-09165-6
|View full text |Cite
|
Sign up to set email alerts
|

T follicular helper cells and antibody response to Hepatitis B virus vaccine in HIV-1 infected children receiving ART

Abstract: HBV vaccine has 95% efficacy in children to prevent HBV infection and related cancer. We conducted a prospective study in HIV-1 infected children receiving ART (n = 49) and controls (n = 63) to assess humoral and cellular responses to HBV vaccine provided with three doses under an accelerated schedule of 4 weeks apart. At 1 month post-vaccination all children, except 4 HIV-1 infected, displayed protective antibody (ab) titers to HBV vaccine; ab titers were lower in infected children (P < 0.0001). Ab titers dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
10
0
1
Order By: Relevance
“…Additionally, analysis of antigen specific Tfh was also not done here. Vaccine antigen-specific Tfh can be detected in germinal center and periphery, nevertheless peripheral antigen specific Tfh detection during chronic infection is difficult 30 , 31 . We were not able to reliably detect HBV antigen specific cytokine production in peripheral Tfh from CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, analysis of antigen specific Tfh was also not done here. Vaccine antigen-specific Tfh can be detected in germinal center and periphery, nevertheless peripheral antigen specific Tfh detection during chronic infection is difficult 30 , 31 . We were not able to reliably detect HBV antigen specific cytokine production in peripheral Tfh from CHB patients.…”
Section: Discussionmentioning
confidence: 99%
“…Others, also reported higher levels of IFN‐γ among patients with ASD compared with controls . Second, Bekele et al showed that HBV‐infected mice and blood from patients with chronic HBV infection contained follicular helper T cells (Tfh cells). These cells consisted of certain phenotypes for producing IFN‐γ, interleukin 2, interleukin 4, and interleukin 21 upon stimulation with HBsAg .…”
Section: Discussionmentioning
confidence: 98%
“…Second, Bekele et al showed that HBV‐infected mice and blood from patients with chronic HBV infection contained follicular helper T cells (Tfh cells). These cells consisted of certain phenotypes for producing IFN‐γ, interleukin 2, interleukin 4, and interleukin 21 upon stimulation with HBsAg . Wang et al also showed that response to HBsAg was blocked by regulatory T cells (Treg cells).…”
Section: Discussionmentioning
confidence: 99%
“…ARV + ) were significantly lower than their unexposed, uninfected counterparts. Several studies have reported reduced childhood HBV vaccine mediated responses in HEI children relative to their negative counterparts [52][53][54][55][56]. However, childhood HBV vaccine mediated responses were significantly higher in HEI.ARV + children than their untreated counterparts (HEI.ARV -).…”
Section: Discussionmentioning
confidence: 99%